Studying The Relationship Between Foreign Direct Investment And Its Determinants For A Sample Of Arab Countries - يسيرة دريباتي,; رولى إسماعيل ,; علي شحاده, (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study examines the relationship between foreign direct investment and its determinants in Syria, Algeria, Morocco and Jordan during the period (1990-2010), using the Auto Regressive Distributed Lag ARDL. The results of the study indicate that the PMG model is the appropriate model, as the model concluded that there is a significant long-term relationship between the independent variables (except for the exchange rate) and foreign direct investment in the study countries, and therefore it is necessary to focus on the importance of determinants and take steps to develop policies that Encourages foreign direct investment. These measures can include developing market size and making laws more attractive to international trade. In addition, steps can be taken to keep inflation rates under control.